INDUSTRY IN THE DIGITAL ECONOMY SUSTAINABLE BASED ON INNOVATIVE DEVELOPMENT ENSURING ECONOMIC GROWTH (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
From the second half of the 20th century to the present day world economy in a new format, i.e. "digital economy" is developing rapidly. 2019 this process The global pandemic of COVID-19 that appeared at the end of the year is one it is not an exaggeration to say that it has accelerated. This especially the management system of real sector enterprises, services, in particular electronic payments and socio-economic communications was evident in the organization.